2022
DOI: 10.3390/s22218538
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Compensation for D-Dot Measurement System in Transient Electromagnetic Pulse Measurement

Abstract: The measurement of the transient pulsed electromagnetic (EM) field is essential for analyzing electromagnetic compatibility. Due to their good performance, D-dot sensors, combined with numerical integration computation for signal recovery, are commonly used to measure electromagnetic pulses (EMPs). However, the integration approach is occasionally flawed due to a non-ideal frequency response or noise, causing distortions in the reconstructed signal. In order to better understand the dynamic performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Figure 11 shows the conceptual structure and equivalent circuit of a typical LPVT with a capacitive voltage divider (CVD) principle based on the C-divider. The LPVT's output can be expressed as the following Equation ( 15) [82].…”
Section: Accuracy Of Evts and Ectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 11 shows the conceptual structure and equivalent circuit of a typical LPVT with a capacitive voltage divider (CVD) principle based on the C-divider. The LPVT's output can be expressed as the following Equation ( 15) [82].…”
Section: Accuracy Of Evts and Ectsmentioning
confidence: 99%
“…Figure 13 shows a block diagram of a typical LPIT. Unlike the EIT describe earlier, derivative output signals are not within the scope of an LPIT according to IE The LPVT's output can be expressed as the following Equation ( 15) [82].…”
Section: Accuracy Of Evts and Ectsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the apparent discharge measured by the EM field sensors was almost identical to the reference PD pulse measured with an oscilloscope. Jin and colleagues [ 32 ] studied the measurement of a transient-pulsed electromagnetic field using a D-dot sensor and outlined a compensation system for the recovery of the incident E-field to improve the dynamic characteristics.…”
Section: Introductionmentioning
confidence: 99%